Enterprising spirit and college students’ creativity: the mediating role of growth mindset, creative tendency and the moderating role of cultural tightness - Ma, Guizhi; Zhou, Silin; Yang, Jiaqin; Man, Xiaotong; Liu, Chunlei (Frontiers in Psychology, 2025)
In an era of innovation-driven development, understanding how to cultivate creativity among college students is crucial. Enterprising spirit, as a key internal driver, is hypothesized to significantly promote creativity, yet its underlying mechanisms and boundary conditions remain underexplored. This study investigates the relationship between enterprising spirit and creativity among 522 college students, exploring the mediating roles of growth mindset and creative tendency and the moderating effect of cultural tightness. Data were collected using validated scales, including the college students’ enterprising spirit questionnaire, the Williams creativity tendency test scale, the cultural tightness–looseness scale, and measures of incremental/radical creativity and growth mindset. Descriptive statistics were conducted utilizing SPSS 26.0, Mediation and moderation effects were analyzed using PROCESS macro v4.0, and correlation network analysis was conducted using R software. The results showed that: (1) Enterprising spirit significantly predicted both incremental and radical creativity. (2) Growth mindset and creative tendency partially mediated this relationship. The indirect effect through growth mindset was significant (3) Cultural tightness moderated the second stage of the mediation path via creative tendency. The moderating effect analysis revealed this indirect effect was stronger in tight cultural environments. These findings reveal a complex mechanism through which enterprising spirit influences creativity, highlighting the interplay between individual factors and socio-cultural context. This study offers theoretical insights for positive psychology and provides practical implications for fostering creativity in higher education.